2018
DOI: 10.1002/jmri.26029
|View full text |Cite
|
Sign up to set email alerts
|

Using multidimensional topological data analysis to identify traits of hip osteoarthritis

Abstract: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:1046-1058.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…This indicates that the thickness of the subtrochanter region may be continuously remodeling to adjust bone architecture to meet the needs of the changing joint in osteoarthritic patients, which could manifest as pain and discomfort. A previous study has used multidimensional data analysis in traits of hip OA and shown that pain changes during different stages of the disease . This further corroborates the need for a longitudinal study, to evaluate pain at different stages of the disease.…”
Section: Discussionsupporting
confidence: 64%
“…This indicates that the thickness of the subtrochanter region may be continuously remodeling to adjust bone architecture to meet the needs of the changing joint in osteoarthritic patients, which could manifest as pain and discomfort. A previous study has used multidimensional data analysis in traits of hip OA and shown that pain changes during different stages of the disease . This further corroborates the need for a longitudinal study, to evaluate pain at different stages of the disease.…”
Section: Discussionsupporting
confidence: 64%
“…After reading complete articles, we excluded 43 articles related to theoretical radiology, 9 to surgery outcomes and robotics, 10 to reeducation outcomes, 45 to molecular biology and 10 to other diseases. We finally selected and analysed 46 articles9 27–72 (online supplemental table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we considered only the relaxation times in the tibia-femoral cartilage for the characterization of OA and included only the age, gender, BMI, and KOOS reported pain scores in the model. OA is whole organ disease that includes other tissues in the joint, specifically their morphological, biochemical, and biomechanical aspect, along with the subjects physical activity levels; the separate analysis of each contributing factor is unable to fully capture the complex nature of this multifactorial disease 35,36 . Thus, further evaluation including the features in the meniscus and bone marrow, along with activity levels, may provide greater insights.…”
Section: Discussionmentioning
confidence: 99%